Empowering the collective reflection-based argumentation mapping strategy to enhance students' argumentative speaking. (July 2022) - Darmawansah, Darmawansah; Lin, Chi-Jen; Hwang, Gwo-Jen
Abstract: It is crucial to design learning strategies for English as Foreign Language (EFL) learners in the context of proliferating and cultivating argumentative speaking. Argumentation mapping aims to provide a visual depiction of collaborative arguments in order to unravel students' engagement in constructing argumentative discussion. The employment of argumentation mapping is fundamental to maintaining students' virtual social practice. However, in the conventional argumentation mapping approach, the acquisition of argumentation skills does not yield successful argumentative dialogue-to-speaking practice. The collective reflection aims to promote a group of learners' reflective thinking and higher order thinking by way of collaborative tasks and group monitoring. This strategy allows students to reflect on their group works when dealing with argumentative knowledge. Hence, this study referred to the educational theory of collective reflection practice and proposed its practice in the Collective Reflection-based Argumentation Mapping (CR-AM) learning strategy. This strategy was applied to an EFL speaking course to enhance students' argumentative speaking. Twenty-four students were recruited as the CR-AM strategy group, with 22 in the conventional Argumentation Mapping (AM) strategy group. The findings indicated that the CR-AM learning strategy could significantly improve students' argumentative speaking performance and their lexical complexity. Although students' critical thinking was at an equivalent level in both groups, students' communication and collaboration tendencies were much higher in the CR-AM strategy group. Based on the argumentation mapping discourse, it was verified that instructing students to extend their activities of classifying collective arguments and monitoring group reflection could effectively support their engagement in argumentation mapping discourse and enhance their argumentation skill performance. Highlights: A collective reflection approach in argumentation mapping was proposed. The approach aimed to enhance students' argumentative speaking based on argument schema theory. An experiment was conducted in an EFL aural-oral drill course. The approach improved students' argumentative speaking performance and lexical complexity. The approach improved students' ill-structured discussion through argumentation mapping.